Cone beam versus conventional computed tomography angiography volume measurement in partial splenic embolization. Issue 5 (February 2019) - Ishikawa, Toru; Imai, Michitaka; Okoshi, Marina; Tomiyoshi, Kei; Kojima, Yuichi; Horigome, Ryoko; Nozawa, Yujiro; Sano, Tomoe; Iwanaga, Akito; Honma, Terasu; Yoshida, Toshiaki
Abstract : Abstract: When performing partial splenic arterial embolization (PSE), it can be difficult to determine the embolization ratio based on 2-dimensional digital subtraction angiography (DSA) image diagnosis alone. Therefore, at our department, we conduct computed tomography (CT) imaging intraoperatively and postoperatively to determine whether the planned embolization has been achieved. In recent years, developments in interventional radiology devices have enabled diagnostic imaging using cone beam CT. Here, we investigated whether the embolization ratio could be predicted from volume measurement with cone beam CT in PSE. We investigated correlations between volume measurement with conventional CT angiography (CTA) and volume measurement with cone beam CTA in 11 cases that underwent PSE with cone beam CT guidance (Allura Clarity FD20; Phillips, Amsterdam, The Netherlands) between December 2013 and May 2018. The mean subject age was 65.0 ± 5.8 years (6 men, 5 women). The subjects had underlying liver disorders of hepatitis C virus infection (4 cases), nonalcoholic steatohepatitis (4 cases), and alcohol-related disease (3 cases). A positive correlation was noted between conventional CTA and cone beam CTA, with infarction rates of 61.28 ± 9.31% and 64.04 ± 9.24%, respectively. The correlation coefficient between the 2 variables was .772. Because blood washout occurs rapidly in the spleen, contrast medium had to be continuously injected during imaging to enable dual-phase imaging with cone beam CT. However, we successfully performed imaging up to the second phase and volume measurement for the embolization ratio by inserting a catheter into the splenic artery and confirming the cone beam CT arrival time from the DSA images. The results were almost identical to those obtained from volume measurement with conventional CT based on CTA imaging. Thus, our results suggest that the splenic embolization ratio measurement obtained via cone beam CTA can be used to assess PSE treatment endpoints.